TRANSFORMASIONAL LEADERSHIP UNTUK MENGEMBANGKAN BUDAYA ORGANISASI YANG INKLUSIF DALAM PENDIDIKAN - Sahdat, Sahdat; Rizhan, Muhammad; Aslamiah, Aslamiah; Cinantya, Celia (STKIP Pesisir Selatan, 2025)
Transformational leadership is not only relevant in the business context but also in education, especially in promoting a more inclusive culture. This study is expected to provide practical implications for educational leaders in implementing effective transformational leadership strategies. Thus, there is a need for further study on how transformational leadership practices can be effectively implemented in schools. This study aims to analyze transformational leadership styles that can facilitate an environment to encourage inclusiveness and diversity. The main focus lies on identifying effective leadership strategies in creating a supportive atmosphere. This study uses a qualitative method with a literature study approach. The results show that the effectiveness of implementing this leadership style is highly dependent on understanding the local context, consistent policy support, and the ability to overcome resistance and resource constraints. Successful inclusive strategies include effective communication, involvement of all stakeholders, continuous learning, and periodic program evaluation. Collaboration between leaders is also key to strengthening implementation and expanding positive impacts.